Digitalisation Readiness of University Students in Erasmus+: A Case Study of Turkey, Italy and Spain - Seda Çankaya; Ömer Kavrar (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Digitalisation, one of the priority areas of the European Commission, has started to show its effects on the digital transformation of the Erasmus+ programme in Higher Education Institutions. In a programme involving by approximately 940 thousand students according to the 2019 figures, the process of handling all mobility-related works in digital platforms is expected to contribute positively to the current workload of higher education institutions. However, it obliges all stakeholders involved in the process to fulfill the requirements for this transformation process. The readiness of the students, who are at the center of this process, is one of the important issues that should be investigated. In this study, it is aimed to comparatively reveal the degree of readiness of the students for the digital transformation of the Erasmus+ programme. In this direction, a questionnaire was applied to a total of 187 students from Spain, Italy, and Turkey, between February and March 2021. In conclusion, the digital skills of the students are one of the most important issues affecting the digital transformation process of the Erasmus+ programme. The level of digital readiness in all three countries are similar since the HEIs are highly interacted by the regulations of Erasmus+ programme.